Electronic data interchange for administration, commerce and transport (EDIFACT). Application level syntax rules (Syntax version number: 4, Syntax release number: 1). Version 3 compatible profile for Version 4 of ISO 9735 Part 11, (19th April 2022) - British Standards Institution,
No abstract available